Combined plasma levels of IL‐10 and testosterone, but not soluble HLA‐G5, predict the risk of death in COVID‐19 patients. (21st November 2022) - Amodio, Giada; Capogrosso, Paolo; Pontillo, Marina; Tassara, Michela; Boeri, Luca; Carenzi, Cristina; Cignoli, Daniele; Ferrara, Anna Maria; Ramirez, Giuseppe A.; Tresoldi, Cristina; Locatelli, Massimo; Santoleri, Luca; et al.
Abstract: Background: The identification of biomarkers correlated with coronavirus disease 2019 (COVID‐19) outcomes is a relevant need for clinical management. Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection is characterized by elevated interleukin (IL)‐6, IL‐10, HLA‐G, and impaired testosterone production. Objectives: We aimed at defining the combined impact of sex hormones, interleukin‐10, and HLA‐G on COVID‐19 pathophysiology and their relationship in male patients. Materials and methods: We measured by chemiluminescence immunoassay, electrochemiluminescent assays, and enzyme‐linked immunosorbent assay circulating total testosterone, 17β‐estradiol (E2 ), IL‐10, and ‐HLAG5 as well as SARS‐CoV‐2 S1/S2 Immunoglobulin G from 292 healthy controls and 111 COVID‐19 patients with different disease severity at hospital admission, and in 53 COVID‐19 patients at 7‐month follow‐up. Results and discussion: We found significantly higher levels of IL‐10, HLA‐G, and E2 in COVID‐19 patients compared to healthy controls and an inverse correlation between IL‐10 and testosterone, with IL‐10, progressively increasing and testosterone progressively decreasing with disease severity. This correlation was lost at the 7‐month follow‐up. The risk of death in COVID‐19 patients with low testosterone increased in the presence of high IL‐10. A negative correlation between SARS‐CoV‐2 Immunoglobulin G and HLA‐G or IL‐10 at hospitalization was observed. At the 7‐month follow‐up, IL‐10 and testosterone normalized, and HLA‐G decreased. Conclusion: Our findings indicate that combined evaluation of IL‐10 and testosterone predicts the risk of death in men with COVID‐19 and support the hypothesis that IL‐10 fails to suppress excessive inflammation by promoting viral spreading.